Bisnis Plan Obat Lambung Fitovarmaka Estomac Health di Indonesia - Hardiansyah, Dera; Hidayat, Fiska Noerina; Sucahyaningsih, Vania; H, Hasim (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The growth of herbal supplement products in Indonesia continues to increase, and EstomacHealth is one such supplement product. This article aims to examine the development and marketing strategies of EstomacHealth through a digital marketing communication approach, particularly by utilizing Key Opinion Leaders (KOL), Key Opinion Consumers (KOC), and Live E-Commerce. The findings show that the combination of health education, KOL credibility, KOC authenticity, and real-time interaction through live streaming can enhance consumer trust, brand awareness, and product sales potential. With positioning as a safe, modern, and affordable herbal gastric supplement, EstomacHealth has strong potential to grow amid competition in Indonesia’s digital health market. Appropriate and sustainable marketing communication strategies are the key factors in building consumer loyalty and achieving long-term business growth.